The Construction of the Image of Madurese Women Through Nature: Ecofeminist Representation in the Poem Ibu by D. Zawawi Imron - Khalili Khalili; Bastian Zulyeno (Badan Pengembangan dan Pembinaan Bahasa, 2026)
This article examines the representation of women’s imagery and its relationship with nature through an ecofeminist reading of the poem “Ibu (Mother)” by D. Zawawi Imron, which strongly presents female figures and nature within the cultural context of Madura, thus having a distinctive and unique character to reveal gender-ecological relations in Indonesian literature. This type of study is a literary text analysis using the close reading technique. The research data consists of the poem Ibu by D. Zawawi Imron as the primary data source. Data collection techniques were carried out through literature review and intensive reading of the text, while data analysis used descriptive-interpretive analysis. This study employs ecofeminist theories proposed by Vandana Shiva (1988) and Val Plumwood (1993), which emphasize the representation of women as ecological subjects who interact harmoniously with nature, challenge patriarchal logic, and affirm gender equality and ecological responsibility as fundamental principles of life. Shiva’s theory is applied to interpret women as subjects aligned with nature, as reflected in their everyday activities that function as the center of ecological meaning in the poem. Meanwhile, Plumwood’s theory of deconstructing dualisms between humans and nature, as well as between men and women, helps to demonstrate how the poem Ibu rejects patriarchal hierarchies by portraying women as integrated with nature rather than subordinated to it. In addition, stylistic analysis is used to examine language style, diction, imagery, and metaphors in order to strengthen the ecofeminist interpretation. The findings indicate that the poet constructs women as ecological agents who assert care and responsibility, both as familial figures and as drivers of socio-economic life and cultural actors, in ways that align with ecofeminist principles. This study contributes to ecofeminist literary studies in Indonesia and strengthens the understanding of the relationship between gender and the environment within local cultural contexts. Abstrak Artikel ini meneliti representasi citra perempuan dan keterkaitannya dengan alam melalui pembacaan ekofeminis terhadap puisi “Ibu” karya D. Zawawi Imron, yang menampilkan figur perempuan dan alam secara kuat dalam konteks budaya Madura, sehingga punya karakter khas dan unik untuk mengungkap relasi gender-ekologi dalam sastra Indonesia. Jenis kajian ini adalah analisis teks sastra dengan teknik pembacaan dekat. Data penelitian berupa teks puisi “Ibu” karya D. Zawawi Imron sebagai sumber data utama. Teknik pengumpulan data dilakukan melalui studi pustaka dan pembacaan intensif terhadap teks, sedangkan teknik analisis data menggunakan analisis deskriptif-interpretatif. Penelitian ini menggunakan teori ekofeminisme Vandana Shiva (1988) dan Val Plumwood (1993), yang menyoroti representasi perempuan sebagai subjek ekologis yang berinteraksi harmonis dengan alam, menolak logika patriarki, serta menegaskan kesetaraan gender dan tanggung jawab ekologis sebagai bagian dari prinsip hidup. Teori Shiva digunakan untuk menafsirkan perempuan sebagai subjek yang selaras dengan alam, yang tercermin dalam aktivitas sehari-hari sebagai pusat makna ekologis dalam puisi. Sementara teori Plumwood tentang dekonstruksi dualisme, manusia dan alam, laki-laki dan perempuan, membantu mengungkap cara puisi “Ibu” menolak hierarki patriarkal melalui penggambaran perempuan yang menyatu dengan alam, bukan ditundukkan olehnya. Selain itu, analisis stilistika digunakan untuk menelaah gaya bahasa, diksi, citraan, dan metafora guna memperkuat interpretasi ekofeminis. Temuan penelitian mengindikasikan bahwa penyair mengonstruksi perempuan sebagai agen ekologis yang menegaskan rasa kepedulian dan tanggung jawab, baik sebagai figur keluarga maupun sebagai penggerak ekonomi sosial dan pelaku budaya, yang sejalan dengan prinsip ekofeminisme. Studi ini berkontribusi pada kajian sastra ekofeminisme di Indonesia dan memperkuat pemahaman tentang hubungan antara gender dan lingkungan dalam konteks budaya lokal.